A review on temperature and humidity effects on Drosophila suzukii population dynamics. (22nd May 2020) - Winkler, Alicia; Jung, Jeanette; Kleinhenz, Benno; Racca, Paolo
Abstract: Drosophila suzukii is an invasive polyphagous pest of wild and cultivated soft‐skinned fruits, which can cause widespread economic damage in orchards and vineyards. The simulation and prediction of D. suzukii's population dynamics would be helpful for guiding pest management. Therefore, we reviewed and summarized the current knowledge on effects of air temperature and relative humidity on different life cycle parameters of D. suzukii . The literature summary presented shows that high oviposition rates can occur between 18 and 30 °C. Temperatures between 16 and 25 °C resulted in fast and high egg‐to‐adult development success of more than 80%. Oviposition and adult life span were positively affected by high relative humidity; however, the factor humidity is so far rarely investigated. We assume that this is one reason why relative humidity usually is not considered in modelling approaches, which are summarized herein. The high number of recently published research articles on D. suzukii 's life cycle suggests that there is already a lot of knowledge available on its biology. However, there are still considerable research gaps mentioned in the literature, which are also summarized herein. Nevertheless, we conclude that sufficient temperature data in the literature are suitable to understand and predict population dynamics of D. suzukii, in order to assist pest management in the field. Abstract : There are substantial data on temperature‐dependent life cycle parameters available in literature to understand and predict D. suzukii population dynamics in order to assist pest management in the field. Indeed, there are already some modelling studies published which almost exclusively use life cycle data based on temperature rather than humidity to predict D. suzukii population dynamics or geographical distribution. However, there are still considerable research gaps mentioned in the literature, e.g. the effect of cold hardening, humidity, host phenology, and natural enemies on D. suzukii population dynamics.